AVALIAÇÃO DA IMPLANTAÇÃO DE UM PROGRAMA DE SEGURANÇA PARA O CONTROLE DOS ACIDENTES NO TRABALHO. UM ESTUDO DE CASO NA INDÚSTRIA QUÍMICA. - Nogueira, Edison Cesar de Faria (2013)
This thesis presents a case study with respect to the implementation of an Occupational Safety Program in a chemical plant, based on the Process Safety Program, PSP, in place in a large energy company. An exploratory qualitative research was conducted gathering data from documents and bibliographic material. This thesis presents the main tasks to be carried out in order for the Safety Program to thrive in a chemical plant, the associated results and input on the better development of the program. The results achieved show that the implementation of a Safety Program must be an ongoing activity, seeking improvement on a continuing basis.